The Effect of Peer Group Influence on Adolescents’ Academic Performance: A Present-Day Challenge - Madonna E. Ayozie; Solomon Justina Adanma Nwagwu; Julia E. Ibebuike; Chinelo Clare Vincent; Anthonia Chinwendu Emesowum; Festa Chinonye Onyekwuo (Research Output Journal of Public Health and Medicine, 2026)
Peer group influence is an important social factor shaping adolescents’ attitudes, behaviors, motivation, and educational outcomes. During adolescence, young people increasingly seek acceptance and recognition from their peers, making peer relationships particularly influential in their academic engagement and performance. This study examines the effect of peer group influence on adolescents’ academic performance, with particular attention to how positive and negative peer interactions affect study habits, school attendance, classroom participation, motivation, and educational achievement. Positive peer influence can encourage collaborative learning, academic competition, information sharing, goal setting, and commitment to schoolwork, whereas negative peer influence may contribute to truancy, poor study habits, distraction, substance use, disruptive behavior, and reduced academic motivation. The contemporary social environment has further complicated peer influence through social media, online communities, and continuous digital interaction, which can extend peer pressure beyond the school environment. The study highlights the importance of family support, teacher guidance, school-based interventions, positive peer networks, and effective adolescent counseling in promoting healthy peer relationships and academic success. Understanding the mechanisms through which peer groups influence educational outcomes is essential for developing interventions that reduce harmful peer pressure while strengthening constructive peer support. Addressing peer influence as a present-day educational and social challenge may contribute to improved academic performance, psychosocial well-being, and successful adolescent development. Keywords: Adolescents; Peer Group Influence; Academic Performance; Peer Pressure; Educational Achievement.